PERENCANAAN INSTALASI PENGOLAHAN LUMPUR TINJA (IPLT) WARA II KOTA AMBON - Anditiaman, Yuliana (Journal of Industrial Process and Chemical Engineering (JOICHE), 2024)
The sewage sludge treatment system at IPLT WARA II, where the physical infrastructure is poorly maintained and management is not running optimally according to Standard Operating Procedures and technical specifications. With the passing years and an increasing population, the volume of sewage sludge predicted does not match the actual volume of sludge produced. The aim of this study is to evaluate the design of the Sludge Separation Chamber and Oxidation Ditch units in IPLT WARA II. The study found that the wastewater flow rate had increased from 100 m³/day to 225 m³/hour. In addition to the flow rate, the design and dimensions of the newly added units in IPLT WARA II were obtained, showing that their implementation is quite efficient with a removal rate of up to 95%. The SSC (Volume = 112 m³, P = 34 m, L = 5 m, Freeboard = 0.5 m), OD (Surface Area = 97 m²), and Clarifier (Volume = 29 m³) were identified. The addition of SSC and OD units as new management strategies ensures that the treatment quality meets environmental standards in accordance with sanitation facility regulations and the Environmental Protection and Management Law. Retribution arrangements have been implemented so that the community and septic tank service companies can make payments in accordance with the local regulation (PERDA).